Examining mechanisms that contribute to relative age effects in pre-pubescent female ice hockey players - Hancock, D. J.; Seal, K.; Young, B. W.; Weir, P. L.; Ste-Marie, D. M. (Talent Development & Excellence, 2013)
Relative age effects (RAEs) in sport often exist when children are grouped into annual age-bands (Barnsley & Thompson, 1988). Recent female studies show different RAE patterns than male sports (Delorme et al., 2010; Weir et al., 2010). Thus, investigations into female RAEs that explain, rather than replicate, RAEs are warranted. One mechanism that ight explain RAEs is physical maturity (Musch & Grondin, 2001). Our purpose was to examine if RAEs were tempered in a pre-pubescent sample (4 to 12 years) where physical maturity differences attributed to puberty are lessened. We used multiple chi-squares to analyze registration data for 39,204 female youth ice hockey players and found RAEs with the highest over-representations in the second quartile. We offer explanations for the results and for why physical maturity differences might not temper RAEs.